Guarda compartilhada: os significados atribuídos por filhas adolescentes - Kostulski, Camila Almeida (2017)
Being the joint custody a recent statutory category in the Brazilian judicial system, it has been causing repercussions in family relationships, especially on the practice of parents’ role and on the possibility of new members joining the family. Thereby, sons need to adapt to this category of custody and to the possible difficulties that might be faced daily in these families. Given that, the research that leaded to this thesis proposed as primary objective to comprehend the meanings assigned by teenage daughters to the experiences on joint custody. For that, it was conducted a qualitative research, using multiple case study. The participants were three adolescent girls and their families, which had been clients of the Núcleo de Assistência Judiciária (Legal Assistance Center), where this research took place and that is an entity associated to a Public University located in the south of Brazil. For data collection, it was used a document analysis of the client’s records in the mentioned institution, the fulfilment of a form with both parents and adolescents and a semi-directive interview conducted with the teenage girls. The data analysis was based on the content analysis. The results of this research are presented and discussed in two articles that are part of this thesis. In the first one, the adolescents express satisfaction with the experiences on joint custody, which allows us to considerate this category of custody as an important strategy for the maintenance of parents’ bounds after marital dissolutions. Besides that, the participants pointed out to some difficulties experienced in the relationships with their parents, however, it seems that these difficulties do not interfere in the joint custody. The second article pointed out, based on the teenage girls narratives, that the mothers are still considered the responsible person by their daughters, however, the fathers, in spite of presenting roles usually more driven to family support, kept present in the care of their daughters. It is emphasized the entrance of stepmothers and stepfathers in family relationships in a non-conflictive way, despite the adolescents narratives pointing out to difficulties that parents experience in relating to new members of the family.